A retrospective analysis of paediatric cases handled by the MSF tele-expertise system - Daniel eMartinez Garcia; Laurent eBONNARDOT; David eOlson; Harriet eRoggeveen; Jaap eKarsten; Peter eMoons; Myrto eSchaefer; Joanne eLiu; Richard eWootton; Richard eWootton (Frontiers in Public Health, 2014)
We conducted a retrospective analysis of all paediatric cases referred by Médecins Sans Frontières (MSF) field doctors via the MSF Telemedicine system during a four-year period from April 2010. A total of 467 paediatric cases were submitted, representing approximately 40% of all telemedicine cases. The median age of the patients was 4 years. The median response time (i.e. the interval between the case being submitted and the first response from a specialist) was 13 hours (interquartile range 4-32 hours). We selected a random sample of 12 paediatric cases in each of four age categories for detailed analysis by an MSF experienced paediatrician. In the 48 randomly-selected cases, the mean rating for the quality of information provided by the referrer was 2.8 (on a scale from 1=very poor to 5=very good), and the mean rating for the appropriateness of the response was 3.3 (same scale). More than two-thirds of the responses were considered to be useful to the patient, and approximately three-quarter were considered to be useful to the medical team. The usefulness of the responses tended to be higher for the medical team than for the patient, and there was some evidence that usefulness to both groups was lower in newborns and adolescent patients. The telemedicine system allows the quality of the medical support given to medical teams in the field to be controlled objectively as there is a record of all cases and answers. Telemedicine has an important role in supporting the aims of medical humanitarian organizations such as MSF.